2020
DOI: 10.3390/nu12020318
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Factors Associated with Disordered Eating between Male and Female Malaysian University Students

Abstract: Disordered eating is prevalent among university students, especially females. Whilst literature suggests that factors associated with disordered eating may differ according to gender, such an association has not been studied in Malaysia. This cross-sectional study aims to compare factors associated with disordered eating between male and female university students. A total of 716 university students (male: 27.4%; female: 72.6%) were recruited in Kuala Lumpur and Selangor, Malaysia. All participants completed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
1
5

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 45 publications
6
23
1
5
Order By: Relevance
“…The present results also indicated that no significant difference was found between women and men in terms of DEA, in opposite to previous studies [ 57 , 58 ] that showed that men had higher levels of DEA compared to women. These findings suggest that DEA could have a similar burden in both genders.…”
Section: Discussioncontrasting
confidence: 99%
“…The present results also indicated that no significant difference was found between women and men in terms of DEA, in opposite to previous studies [ 57 , 58 ] that showed that men had higher levels of DEA compared to women. These findings suggest that DEA could have a similar burden in both genders.…”
Section: Discussioncontrasting
confidence: 99%
“…Of the 34 articles found, 27 studies [29][30][31][32][33][34][35][36][37][38][39][40][41][44][45][46][47][48]51,52,[55][56][57][58][59][60][61] were conducted in single nations, and 7 were 42,43,49,50,53,54,63 multinational studies. Most of the studies assessed depression, anxiety, and stress.…”
Section: Resultsmentioning
confidence: 99%
“…42,44,47 Disordered eating was correlated with PTSD in one study, 48 and with depression in other studies. 49,58,60 Internet addiction/pathological use was identified as a predictor for depression 51 and eating disorder. 49 On the contrary, high scores of anxiety and depression predicted problematic Internet use.…”
Section: Determinants Of Mental Health and Psychiatric Comorbiditiesmentioning
confidence: 99%
“…In summary, previous studies have revealed that disordered eating is determined by individual factors such as weight and body shape concerns [ 60 , 61 ]; emotional distress [ 28 , 29 , 62 ]; by interpersonal factors, such as family influences [ 32 , 33 ]; by peer relationships and negative responses from close ones [ 23 , 49 , 50 ]; and by macro-level environmental factors such as media and societal expectations [ 32 ]. This study adopted a multifaceted factor approach to examine gender-specific responses to multifaceted factors associated with disordered eating, including personal, behavioral, family, and school-related characteristics [ 23 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%